2018
DOI: 10.1016/j.biortech.2018.07.068
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol production from lignocellulosic whole slurry corn cob by engineered industrial Saccharomyces cerevisiae PE-2

Abstract: In this work, the industrial Saccharomyces cerevisiae PE-2 strain, presenting innate capacity for xylitol accumulation, was engineered for xylitol production by overexpression of the endogenous GRE3 gene and expression of different xylose reductases from Pichia stipitis. The best-performing GRE3-overexpressing strain was capable to produce 148.5 g/L of xylitol from high xylose-containing media, with a 0.95 g/g yield, and maintained close to maximum theoretical yields (0.89 g/g) when tested in non-detoxified co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 50 publications
1
55
0
1
Order By: Relevance
“…The pretreatment severity was based on previous works that have shown that the use of 12 g of corn cob per 100 g of water lead to maximum concentration of xylooligosaccharides (Garrote et al, 2008;Rivas et al, 2006). In order to reduce the water consumption in the process and increase the xylose concentration in the liquid fraction (hydrolysate), the solid loading of corn cob was evaluated in the range of 20 to 30 g of corn cob per 100 g of water at T max of 205°C (S 0 = 3.89) (Baptista et al, 2018). The use of high-solid loadings in the pretreatment minimizes the water consumption and reduces the energy required for heating, improving the economic and environmental sustainability of the process (Modenbach and Nokes, 2012; Jesus et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pretreatment severity was based on previous works that have shown that the use of 12 g of corn cob per 100 g of water lead to maximum concentration of xylooligosaccharides (Garrote et al, 2008;Rivas et al, 2006). In order to reduce the water consumption in the process and increase the xylose concentration in the liquid fraction (hydrolysate), the solid loading of corn cob was evaluated in the range of 20 to 30 g of corn cob per 100 g of water at T max of 205°C (S 0 = 3.89) (Baptista et al, 2018). The use of high-solid loadings in the pretreatment minimizes the water consumption and reduces the energy required for heating, improving the economic and environmental sustainability of the process (Modenbach and Nokes, 2012; Jesus et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The yeast strain used in this work was the yeast strain Saccharomyces cerevisiae PE-2, isolated from 1 st generation bioethanol plants in Brazil, (Basso et al, 2008;Pereira et al, 2014aPereira et al, , 2014bPereira et al, 2011Pereira et al, , 2010 overexpressing the endogenous GRE3 gene, S. cerevisiae PE-2-GRE3 (Baptista et al, 2018). Yeast strain was maintained at 4°C on YPD plates (10 g/L yeast extract, 20 g/L peptone, 20 g/L glucose and 20 g/L agar) supplemented with 200 mg/L of geneticin (G418).…”
Section: Yeast Strain and Inoculummentioning
confidence: 99%
See 2 more Smart Citations
“…Since the dry mass content is generally less than 13%, the xylose concentration after hydrolysis of corn stover was reported to be 16.4-20.5 g/L [10,34]. However, a significantly higher substrate (xylose) concentration of about 200 g/L is required for xylitol production [35,36]. Vacuum evaporation concentration is undesirable, due to its high energy consuming and generation of inhibitors such as furfural and hydroxyl methyl furfural (HMF).…”
Section: Introductionmentioning
confidence: 99%